Dissolved Oxygen Based Carrying Capacity in the Sungai Paku Reservoir in the KamparKiri Sub-District, Kampar District, Riau Province - Dewi, Afrila; Simarmata, Asmika Harnalin; Siagian, Madju (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractCarrying capacity is an ability of aquatic environment to support the life of aquatic organisms and it can be determined based on dissolved oxygen concentration. To understand the dissolved oxygen based carrying capacity in the Sungai Paku reservoir, a research has been conducted in June-July 2019. Water samples were taken in three stations, Station 1 (riverine zone), Station 2 (transition zone) and Station 3 in the floating cage area (lacustrine zone). In  each station, there were 3 sampling points, in the surface, in the 2 Secchi depth and in the 4 Secchi depth was done once/week. Water quality parameters measured were dissolved oxygen, CO2, pH, temperature, transparency, depth, nitrate and phosphate. Carrying capacity was then analyzed. Result shown that DO concentration was 4.60-5.88 mg/L, in the surface, 3.77-4.64 mg/L in 2 Secchi depth and 2.08-2.93 mg/L in 4 Secchi depth. Water quality parameters were as follows: depth was 4-6 m, transparency was 69.1-80.8 cm, temperature was 29-30oC, pH was 5, CO2 was 7.92-15.42 mg/L, nitrate was 0.075-0.140 mg/L and phosphate was 0.065-0.0134 mg/L. The dissolved oxygen based carrying capacity in the Sungai Paku Reservoir is 2,032 kg/year and the number of fish cage that can be placed in the dam was 8 units (5 x 5 x 3 m).Keywords :  Dissolved oxygen, Floating cage, Sungai Paku Dam, Water quality